2008
DOI: 10.1139/t08-076
|View full text |Cite
|
Sign up to set email alerts
|

Modelling landfill leachate-induced clogging of field-scale test cells (mesocosms)

Abstract: A two-dimensional fluid flow and reactive transport model, BioClog, created to predict clogging in landfill leachate collection systems is used to calculate the clogging of gravel and treatment of leachate as it flows through the gravel in two real-scale experimental cells, called mesocosms, which represent the portion of a landfill drainage layer adjacent to a landfill collection pipe. These tests were conducted using real-time flows of landfill leachate and were run for about 6 and 12 years. The model comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…For the granular drainage layers, uniformly graded gravel with grain sizes d g ¼ 6 and 27 mm were modeled with the coarser (27 mm) gravel as the base. The initial porosity of the granular material with the grain size d g ¼ 27 mm was 0.41 and the initial hydraulic conductivity was 0.12 m=s (Cooke and Rowe 2008b). For the grain size d g ¼ 6 mm, the initial porosity and hydraulic conductivity were 0.39 and 0.05 m=s, respectively, as in the study by Cooke and Rowe (2008a).…”
Section: Model Summarymentioning
confidence: 53%
“…For the granular drainage layers, uniformly graded gravel with grain sizes d g ¼ 6 and 27 mm were modeled with the coarser (27 mm) gravel as the base. The initial porosity of the granular material with the grain size d g ¼ 27 mm was 0.41 and the initial hydraulic conductivity was 0.12 m=s (Cooke and Rowe 2008b). For the grain size d g ¼ 6 mm, the initial porosity and hydraulic conductivity were 0.39 and 0.05 m=s, respectively, as in the study by Cooke and Rowe (2008a).…”
Section: Model Summarymentioning
confidence: 53%
“…For modelling the leachate transport and clog mass accumulation within the porous, a numerical model 'BioClog' was first developed by Cooke et al [4] and subsequently updated after five years by Cooke and Rowe [3]. BioClog first was created 1D model and used by Cooke et al [4].…”
mentioning
confidence: 99%
“…The calculated amount of clog mass within the columns coincided well with the measured laboratory results. Cooke and Rowe [3] employed BioClog-2D to model mesocosms and found that te model estimated the clog mass well in the upper regions of the saturated drainage layer but underestimated the clogging in the lower regions of saturated drainage layer [6].…”
mentioning
confidence: 99%
See 2 more Smart Citations